2020
DOI: 10.1186/s12864-020-6475-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide survey and expression analysis of calcium-dependent protein kinase (CDPK) in grass Brachypodium distachyon

Abstract: Background: Ca 2+ played as a ubiquitous secondary messenger involved in plant growth, development, and responses to various environmental stimuli. Calcium-dependent protein kinases (CDPK) were important Ca 2+ sensors, which could directly translate Ca 2+ signals into downstream phosphorylation signals. Considering the importance of CDPKs as Ca 2+ effectors for regulation of plant stress tolerance and few studies on Brachypodium distachyon were available, it was of interest for us to isolate CDPKs from B. dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 112 publications
0
19
0
Order By: Relevance
“…The homolog of Gorai.010G168400 in Arabidopsis, encoding AtOSCA3.1 protein, acts as a hyperosmolarity-gated non-selective cation channel that permeates Ca 2+ ions [31]. And Gorai.010G168400, showed a higher expression level under salt and cold stress compared to control groups, was a potential sensor that mediates cold and salt stress in cotton, and calcium ion plays an important role in abiotic stress response as the second messenger [32].…”
Section: Discussionmentioning
confidence: 99%
“…The homolog of Gorai.010G168400 in Arabidopsis, encoding AtOSCA3.1 protein, acts as a hyperosmolarity-gated non-selective cation channel that permeates Ca 2+ ions [31]. And Gorai.010G168400, showed a higher expression level under salt and cold stress compared to control groups, was a potential sensor that mediates cold and salt stress in cotton, and calcium ion plays an important role in abiotic stress response as the second messenger [32].…”
Section: Discussionmentioning
confidence: 99%
“…The homolog of Gorai.010G168400 in Arabidopsis, encoding AtOSCA3.1 protein, play a role in the hyperosmolarity-gated non-selective cation channel that permeates Ca 2+ ions [31]. And Gorai.010G168400, showed a higher expression level under salt and cold stress compared to control groups, was a potential sensor that mediates cold and salt stress in cotton, and calcium ion acts as the second messengers in response to abiotic stress [32]. Gorai.009G294400, encoding CBL-interacting protein kinase 18, which involved in Ca 2+ signal transduction, was also found that different express under cold and salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…During the wheat grain filling period (from 22 April to 31 May) in 2015, our lab performed a quantitative proteomics to characterize the genome-scale grain protein expression profiles of the bread wheat cultivar Zhoumai 18 at different grain filling stages (5,10,15,20,25,30, and 35 days after anthesis) under field conditions [17]. During the late stages of wheat grain filling period (from 6 to 31 May, 2015, corresponding to 15~35 days after anthesis), there was only 25.5 mm rainfall, which was enough for wheat growth and caused drought stress in this growth season (Table S1).…”
Section: Identification Of Tacpk34mentioning
confidence: 99%
“…2), suggesting that they could have similar mechanisms. AtCPK10 has been found to interact with HSP1 and participate the drought tolerance through the modulation of ABA-and Ca 2+ -mediated stomatal movements [10]. OsCPK4 enhances the drought tolerance through reducing membrane lipid peroxidation in rice, possibly by upregulating a number of genes associated with the lipid metabolism [36].…”
Section: Tacpk34 Could Regulate Expression Of the Target Genes In Resmentioning
confidence: 99%
See 1 more Smart Citation